THE ROLE OF CORPORATE CULTURE IN RAISING THE PROFESSIONAL COMPETENCE OF PUBLIC SERVANTS AND LOCAL GOVERNMENT OFFICIALS IN TERMS OF PUBLIC ADMINISTRATION REFORM - Shcherbak N.V. (Pressing Problems of Public Administration, 2016)
The article highlights main issues of increasing the level of the professional competence of the civil servants and the local elected representatives. By study and analysis of the experiences of other European countries, best national and international practices on public administration reform, the role of the corporative culture in the process of retraining of the civil servants and the local elected representatives is highlighted.